Use of technologies by nurses in the management of primary health care - Bruno César Gomes Fernandes; José Nildo de Barros Silva Júnior; Haline Costa dos Santos Guedes; Diego Bruno Gonçalves Macedo; Matheus Figueiredo Nogueira; Anne Jaquelyne Roque Barrêto
ABSTRACT Objective To analyze the management actions of nurses in Primary Health Care services from the perspective of technologies. Method Descriptive-exploratory study with a quantitative approach, carried out from February to April 2019. Through the snowball technique, the sample consisted of 42 nurses from Primary Health Care, using an electronic tool for data collection. The data were analyzed using descriptive statistics techniques. Results 54.8% of nurses use technologies through SISREG and PEC electronic systems, care training related to permanent health education, online and face-to-face courses, in addition to care technologies such as telehealth and telemedicine. Conclusion Management actions focused on technology showed restricted use. Nurses need to empower themselves with these organizational devices, with the aim of improving the provision and quality of care for users.